Rowing Injuries in Elite Athletes: A Review of Incidence with Risk Factors and the Role of Biomechanics in Its Management - Arumugam, S. (Indian J Orthop, 2020)
BACKGROUND: Rowing is an Olympic sport gaining popularity in India and injuries are common in these athletes. Determinants of performance, injury risk and training are all interrelated in rowing. Injuries result from various risk factors including fitness issues and improper techniques. Rowers should have adequate leg extension strength and lumbo-pelvic coordination to produce and transmit power from the legs to the oar handle. Biomechanical analysis of the rowing stroke can help in preventing injuries and optimise technique for best performance. It involves a detailed and systematic observation of movement patterns to establish the quality of the movement and provide feedback to the rower about the key variables affecting performance and injury risk. Kinetics such as foot forces and kinematics such as key joint angles can be accurately measured by instrumented foot stretcher and three-dimensional motion capture. AIM: To do a detailed review of literature regarding the incidence and risk factors for rowing injuries and to get an insight on the role of biomechanics in its management. MATERIALS AND METHODS: Literature review was carried out with standard academic search engines and databases including Science Direct, PubMed and Google Scholar using keywords of relevance. A total number of 38 articles were analysed and results were collated to compile this review report. RESULTS: Lumbar spine is most commonly injured (up to 53%), followed by rib cage (9–10%) and shoulder and other anatomical areas. Rowers with a trunk-driven rowing action will have a lower hip:trunk score and carry a high injury risk. A player with lumbar injury will take a minimum of 3–4 months to recover. CONCLUSION: Rowing injuries are common. Regular screening of the rowing athletes by comprehensive fitness and biomechanics assessment will help in prevention of injuries. Rowers need to be tested for pain, strength, flexibility, reproducibility of rowing action with modified mechanics, coordination, fatigue level, explosive power, aerobic and anaerobic endurance. Early recognition of risk factors and timely intervention is the key aspect of a successful return to play.